2018
DOI: 10.1021/acs.jpcc.7b11157
|View full text |Cite
|
Sign up to set email alerts
|

Ability To Fine-Tune the Electronic Properties and Open-Circuit Voltage of Phenoxy-Boron Subphthalocyanines through Meta-Fluorination of the Axial Substituent

Abstract: Six different boron subphthalocyanines with fluorophenoxy axial substituents were synthesized to explore and fine-tune the HOMO and LUMO energy levels based on past observations of the unique levels of pentafluorophenoxy-boron subphthalocyanine (F5BsubPc). Electrochemistry reduction potentials, ionization energies from ultraviolet photoelectron spectroscopy (UPS) measurements, and energy levels calculated using semiempirical methods reveal finely variable values between phenoxy-BsubPc (PhO-BsubPc), without any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 50 publications
4
52
0
Order By: Relevance
“…This effect is also true for some phenoxylated BsubPcs. 27,39 The reversibility in both the oxidation and reduction region for the phenoxy Cl n BsubNcs is not overly surprising as the aromatic nature of the axial substituent combined with the more π-extended benzoisoindoline subunits are anticipated to stabilize the BsubNc in its radical anion or radical cation form. Differential pulse voltammetry (DPV, degassed DMF, 0.1 M TBAPC) was also carried out and it verified the CV results (Figure S8 and Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…This effect is also true for some phenoxylated BsubPcs. 27,39 The reversibility in both the oxidation and reduction region for the phenoxy Cl n BsubNcs is not overly surprising as the aromatic nature of the axial substituent combined with the more π-extended benzoisoindoline subunits are anticipated to stabilize the BsubNc in its radical anion or radical cation form. Differential pulse voltammetry (DPV, degassed DMF, 0.1 M TBAPC) was also carried out and it verified the CV results (Figure S8 and Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…The subscript R is the reference fluorophore, F 5 PhO-BsubPc, with a reported Φ = 0.42 [9] in toluene at room temperature. This is a standard operating procedure from literature [32] and well established in our laboratory [9,33] for a series of BsubPcs; however, it has been revised for this study to extend the measurements for a wide range of BsubPcs with various maximum absorbance shifts in energy. Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were carried out using a Bioanalytical Systems C3 electrochemical workstation (unless otherwise stated, specifically for CV traces stacked in Figure S6 and the data collated in Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Results demonstrated that α‐6T is suitable as a standard electron donor to pair with BsubPc derivatives in vacuum deposited PHJ devices, with even α‐6T/Cl‐Cl 6 BsubPc outperforming α‐6T/C 60 despite significant V OC losses. Several novel BsubPc derivatives were synthesized and paired with an α‐6T in subsequent studies . The ability to fine‐tune the V OC through peripheral chlorination was also demonstrated, although pairing α‐6T with BsubPcs with deep LUMO energy levels (Cl‐Cl 6 BsubPc, Cl‐Cl 12 BsubPc) substantially reduces the V OC and overall OPV performance.…”
Section: Boron Subphthalocyaninesmentioning
confidence: 99%
“…An array of fluorophenoxy‐BsubPc (F n PhO‐BsubPc) compounds (Figure b ) ) were synthesized to investigate tunability of the HOMO/LUMO energy levels and electronic properties . The meta position was discovered to be the sole influencer on HOMO/LUMO, effectively dividing the array of F n PhO‐BsubPcs into two “buckets”.…”
Section: Boron Subphthalocyaninesmentioning
confidence: 99%